Three Presidents and an Aide : Life, Power and Politics - Khan, Arshad Sami, Ambassador, 1942-; Edited by Sharma A. K. (New Delhi Pentagon Press, 2008)
Memoirs of the author, a Pakistani diplomat.
Include Illustration (Page 1-16) and Index
Keywords: Pakistan -- Politics and government